'The Leaning Tower of Pizzazz': Ted Tinling, couturier for the women's professional tennis revolution. Issue 3 (1st October 2016) - Tredway, Kristi
From 1947 until his death in 1990, Ted Tinling created couture fashion pieces for the world's top tennis stars. A dressmaker in London's famed Mayfair fashion district, Tinling turned to women's tennis fashion after World War II due to the constraints on his creativity that the post-war rationing of goods caused. Tinling created some of the most notable dresses in tennis fashion, including Gussy Moran's dress and lace bloomers that shocked the Wimbledon crowds in 1949 and Billie Jean King's 'Battle of the Sexes' dress in 1973, which she wore as she defeated Bobby Riggs. His compulsion to push the limits of fashion, no matter how much the powers that be are offended, made him a couturier that will never be replicated. Tinling's fashions, with their veil of femininity, allowed female athletes to compete unencumbered by cultural expectations. This would be Tinling's greatest feat.